2012
DOI: 10.1161/circulationaha.111.048041
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Cytoplasmic Loops of the KCNQ1 Channel and the Risk of Life-Threatening Events

Abstract: Background β-adrenergic stimulation is the main trigger for cardiac events in type-1 long QT syndrome (LQT1). We evaluated a possible association between ion channel response to β-adrenergic stimulation and clinical response to β-blocker therapy according to mutation location. Methods and Results The study sample comprised 860 patients with genetically-confirmed mutations in the KCNQ1 channel. Patients were categorized into carriers of missense mutations located in the cytoplasmic loops (C-loops), membrane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 186 publications
(92 citation statements)
references
References 30 publications
5
76
1
1
Order By: Relevance
“…The percentage of KCNQ1 mutations located in the small C-loop region is hard to define; it likely corresponds to a small proportion of probands. According to the Gene Connection for the Heart database (www.fsm.it/cardmoc), of 357 KCNQ1 mutations, only 54 (15%) are in the C loop ( Figure 1); this number confirms the estimate reported in the study by Barsheshet et al 15 A most interesting part of the study relates to the in vitro characterization of KCNQ1 mutations. Functional investigations performed by the authors show that, analogous to what observed in all LQTS-related mutations in the KCNQ1 gene, the I Ks current is decreased in all the C-loop mutations.…”
Section: Article See P 1988supporting
confidence: 80%
“…The percentage of KCNQ1 mutations located in the small C-loop region is hard to define; it likely corresponds to a small proportion of probands. According to the Gene Connection for the Heart database (www.fsm.it/cardmoc), of 357 KCNQ1 mutations, only 54 (15%) are in the C loop ( Figure 1); this number confirms the estimate reported in the study by Barsheshet et al 15 A most interesting part of the study relates to the in vitro characterization of KCNQ1 mutations. Functional investigations performed by the authors show that, analogous to what observed in all LQTS-related mutations in the KCNQ1 gene, the I Ks current is decreased in all the C-loop mutations.…”
Section: Article See P 1988supporting
confidence: 80%
“…W innych chorobach, takich jak zespół Brugadów lub zespół krótkiego odstępu QT (SQTS), stratyfikacja ryzyka nie jest tak pewna, co pozostawia wątpliwości, u kogo profilaktycznie wszczepiać ICD. Informacje genetyczne można obecnie wykorzystywać do stratyfikacji ryzyka tylko w kilku chorobach, takich jak LQTS oraz kardiomiopatia rozstrzeniowa (DCM) związana z mutacjami genu laminy A/C (LMNA) [69][70][71].…”
Section: Pacjenci Z Dziedzicznymi Chorobami Arytmogennymiunclassified
“…In patients with LQT1, missense cytoplasmic-loop mutations have been reported to cause a longer QT interval at enrolment and an increased risk of ACA/SCD. 71 As a specific mutation in KCNQ1, A341V, more than other KCNQ1 mutations (transmembrane tomatic patients who are refractory to β-blocker therapy. LCSD has been shown to reduce cardiac events significantly in LQTS with a rather high long-term cardiac-event-free survival (46%/5 years, 91 59%/2 years 92 ).…”
Section: Risk Assessment Of Cardiac Eventsmentioning
confidence: 99%